Analysis of total factor productivity growth in Singapore manufacturing industry : 1990-2007 - Xiao, Longhui (2010)
This study aims to find out the performance of Total Factor Productivity (TFP) in Singapore Manufacturing industry over the period of 1990 to 2007 and the determinant of TFP growth, especially in eight sub sectors. Firstly, TFP growth is estimated from industry level data. Then regression analysis is conducted based on a series of equations. The TFP growth is estimated to be 1.5% per annum, with an improved performance of 4.5% from 1995 to 2006. Moreover, capital-intensity is found to have insignificant influence on TFP growth. Learn-by-doing effect is also insignificant in manufacturing industry. System of equations about unit labour cost, labour productivity and capital intensity is analyzed by regression method and significant negative effect of labour productivity on unit labour cost is found.